Synthesis, structural and in vitro biological evaluation of diamondoid-decorated lipophilic organotin(IV) derivatives - Basu Baul, Tushar S.; Manne, Rajesh; Duthie, Andrew; Liew, Li Yuan *; Chew, Jactty *; Lee, See Mun *; Tiekink, Edward R. T. * (Elsevier, 2021)
A series of diamondoid-decorated organotin(IV) derivatives of composition Me3Sn(L1) (1), Ph3Sn(L1) (2), {[Me2Sn(L1)]2O}2 (3), [BzSn(O)(L1)]6 (4), Me3Sn(L2)OH2 (5), [Ph3Sn(L2)]n (6), Bu2Sn(L2)2 (7), Bz2Sn(L2)2OH2 (8) and [BzSn(O)(L2)]6 (9) were prepared by reacting appropriate organotin(IV) precursors with either acid forms of the pro-ligands adamantane-1-carboxylic acid (HL1) and 2-(adamantan-1-yl)acetic acid (HL2) or their sodium salts. Compounds 1-9 were characterised by spectroscopic techniques, including 119Sn NMR in non-coordinating solvent for assessment of the solution-state structures. The molecular and crystal structures of 2-8 were established by X-ray crystallography. The packing is largely dictated by hydrophobic interactions with the exception in the crystals of 6, where Sn…O secondary bonding is apparent, and in each of 5 and 8 where O–H…O hydrogen bonding is present leading to a two-dimensional array and zig-zag chains, respectively. The organotin compounds were evaluated for their anti-bacterial activity against 15 human bacterial pathogens. Based on disc diffusion and minimum inhibitory concentration assays, the two triphenyltin species, 2 and 6, and di-n-butyl species, 7, are effective against both Gram-positive and Gram-negative bacteria, including methicillin resistant Staphylococcus aureus (MTCC 381123) and Shigella flexneri (ATCC 12022), a causative agent for shigellosis. Time-kill assays showed that 2 and 6 had both time- and concentration-dependent anti-bacterial effects against susceptible bacteria. Cell viability assays showed that 2 and 6 were moderately toxic to a normal cell line, that is, human embryonic kidney 293T (HEK293T).